2021
DOI: 10.1002/pssa.202000698
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Dissipation Annealing for Crystallization of In‐Doped ZnO Films Deposited on Polyethylene Naphthalate Substrate without Substrate Deformation

Abstract: High‐temperature annealing is essential to crystallize sol–gel spin‐coated ZnO films but is a critical disadvantage in manufacturing flexible and transparent electronics, owing to low thermal stability of polymer substrates. Thus, a novel annealing method, named thermal dissipation annealing (TDA), is developed. TDA method can anneal ZnO films without any deformation of polymer substrates. The effects of TDA method are confirmed by annealing ZnO films deposited on glass and polyethylene naphthalate substrates.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Noted that the response current saturating in a few minutes is usually observed in metal oxide based photodetectors. [59][60][61][62][63] The response speed is not fast, but is sufficient in colorimetric biosensing. Then, in Figure 6c, we plotted the ΔI-equivalent urea concentration relation measured by 515 nm LED as the calibration curve (black curve).…”
Section: Integrated 3d-printed Sensing Chamber For Colorimetric Urea ...mentioning
confidence: 99%
“…Noted that the response current saturating in a few minutes is usually observed in metal oxide based photodetectors. [59][60][61][62][63] The response speed is not fast, but is sufficient in colorimetric biosensing. Then, in Figure 6c, we plotted the ΔI-equivalent urea concentration relation measured by 515 nm LED as the calibration curve (black curve).…”
Section: Integrated 3d-printed Sensing Chamber For Colorimetric Urea ...mentioning
confidence: 99%
“…It is found that doping significantly reduces trap defects and promotes charge separation, which leads to improved PCE of PSCs. Aluminum (Al), boron (B), indium (In), and gallium (Ga) are among the most commonly used dopants for ZnO. ,,,, For instance, Mahmood et al demonstrated a PSC with a PCE of 17.18% using In-doped ZnO ETL, and Tseng et al improved PSC’s PCE to 17.6% using Al-doped ZnO ETL. , However, Al can oxidize and form aluminum oxide or alumina (Al 2 O 3 ), which can create grain boundaries and defects that limit the PCE of PSCs . On the other hand, dopants such as gallium, magnesium, lithium, and cobalt have been used, but no significant improvement in the PCE of the PSCs has been achieved. Thus, tungsten (W) is a promising candidate for the development of doped ZnO ETLs, which shows excellent promise for the realization of efficient PSCs due to its low reactivity and similar ionic radius as Zn 2+ (0.074 nm) and W 6+ (0.064 nm). , These properties of ZnO:W eliminate the lattice distortion of the wurtzite structure ZnO.…”
Section: Introductionmentioning
confidence: 99%
“…35,41 However, Al can oxidize and form aluminum oxide or alumina (Al 2 O 3 ), which can create grain boundaries and defects that limit the PCE of PSCs. 42 On the other hand, dopants such as gallium, magnesium, lithium, and cobalt have been used, but no significant improvement in the PCE of the PSCs has been achieved. 43−46 Thus, tungsten (W) is a promising candidate for the development of doped ZnO ETLs, which shows excellent promise for the realization of efficient PSCs due to its low reactivity and similar ionic radius as Zn 2+ (0.074 nm) and W 6+ (0.064 nm).…”
Section: Introductionmentioning
confidence: 99%